Kudumbashree: Microcredit Alternative - Thomas Isaac T.M
T h e p a p e r i s t h e r e - r e n d e r i n g o f t h e s p e e c h d e l i v e r e d b y t h e a u t h o r, F o r m e r F e l l o w, C e n t r e f o r D e v e l o p m e n t S t u d i e s , India w h i l e h e w a s i n a u g u r a t i n g t h e Inter national Conference on Micro -finance: Gender and Pover ty organized by SCMS- COCHIN in association with the University of Central Lancashire, UK in December 2009. In it the author scans the activities of Kudumbashree with a massive membership of 3.7 million women belonging to the weaker section. Microfinance, a tiny tag for micro-financial services, is a pristine product in spite of its being the rebir th of a patter n once existed. The author owing to his lef tist leanings does not forget to give a dig at the machination of the World Bank concer ns with spurs on such deliberations all over the world, kindling controversies and bringing in capitalist taste